Challenges in the use of antibiotics and resistance pattern of odontogenic mandibular abscess: a systematic review - Anggraini, Santi; Damanhuri, Rahma Yulinda; Silviany, Rika; Ripen, Zakiah Mat (Padjadjaran Journal of Dentistry, 2025)
Introduction: Odontogenic mandibular abscess is a severe and potentially life-threatening dental infection that demands prompt and appropriate intervention. Previous reviews have focused broadly on odontogenic infections, but few have analyzed antibiotic resistance trends specific to mandibular abscesses. This systematic review aims to evaluate the effectiveness of antibiotic therapy and to analyze current antimicrobial resistance patterns in the management of odontogenic mandibular abscesses. Methods: The research question was framed using the PICOS approach; Participants: patients with odontogenic mandibular abscess; Interventions: antibiotic regimens; Comparisons: different antibiotics or combinations; Outcomes: cure rate, duration, complications, and resistance; Study design: clinical, observational, or randomized controlled trials. Literature was searched systematically in PubMed, Scopus, Web of Science, and Cochrane Library for studies published between 2014 and 2024. Previously published systematic reviews and case reports were excluded. Results: Ten studies met the inclusion criteria (six prospective cohorts, three retrospective, and one randomized controlled trial). The predominant pathogens were Klebsiella pneumoniae (42%), Streptococcus spp. (38%), and Staphylococcus spp. (35%). Empirical antibiotic combinations of ceftriaxone-metronidazole and amoxicillin-metronidazole showed clinical success rates of 85% and 78%, respectively. Resistance was highest for amoxicillin (67%) and ampicillin (72%), while amikacin and meropenem demonstrated high sensitivity (>90%). Conclusion: Misuse of antibiotics remains a major contributor to antimicrobial resistance. Optimal management of odontogenic mandibular abscesses requires surgical drainage combined with rational antibiotic use based on resistance data. The implication of this systematic review is to provide evidence-based guidance for antibiotic selection, supporting antibiotic stewardship and improved clinical outcomes.